Extreme 13C-depletions and organic sulfur content argue for S-fueled anaerobic methane oxidation in 2.72 Ga old stromatolites. (1st January 2019) - Lepot, Kevin; Williford, Kenneth H.; Philippot, Pascal; Thomazo, Christophe; Ushikubo, Takayuki; Kitajima, Kouki; Mostefaoui, Smaïl; Valley, John W.
Abstract: The extreme 13 C-depletions recorded in Neoarchean organic matter (OM) have commonly been interpreted as markers of methanotrophy. This methane oxidation metabolism could have been performed using oxidants such as dioxygen, sulfate, nitrite/nitrate, and/or Fe 3+ - and Mn 4+ -minerals. Acetogenesis using acetyl-CoA metabolism may produce similar 13 C-depletions. We investigated δ 13 C and S/C values of OM in 2.72 Ga old lacustrine stromatolites of the Tumbiana Formation (Australia) using Secondary Ion Mass Spectrometry (SIMS), coupled with X-ray spectroscopy. Type-A OM is embedded in quartz and/or chlorite. We show that mixtures of chlorite bias negatively the δ 13 Corg of associated OM measured by SIMS, likely through recombination of hydrogen from chlorite with carbon from OM during analysis. Type-A OM, associated with quartz or interleaved with chlorites (but remote enough to avoid H-recombination), displays δ 13 Corg between −56.1 and −50.6‰ VPDB (mean: −53.5‰, SD ± 1.8‰). The intimate association of Type-A OM with Fe-rich chlorite and its main occurrence in pyritic layers coupled with 13 C-depletions is most parsimoniously interpreted as anaerobic methanotrophy using Fe 3+ -minerals and/or oxidized S. Type-B OM comprises <2-µm organic globules embedded in calcite. A mass balance correction using the δ 13 C values measured on Type-B globules mixed with calcite and those measured on pure calcite yielded corrected δ 13 C∗org values for the globules ranging between −65.2 and −52.5‰ (mean −58.8‰, SD ± 3.6‰). In a context where Fe and S reduction could outcompete acetogenesis for a fraction of any available H2, these extremely low δ 13 Corg values are difficult to explain with chemoautotrophic acetogenesis. Atomic S/C ratios in Type-B globules reach up to 0.042, i.e. up to tenfold the values (0.003–0.004) in Type A-OM. These organic S concentrations, combined with the extremely low δ 13 C∗org values, support anaerobic oxidation of methane coupled to sulfur oxidation. Finally, Type-C OM, interpreted as migrated pyrobitumen nodules, displays δ 13 Corg of −48 to −39.1‰. The most extreme low-δ 13 Corg values of the Precambrian are thus best interpreted as the result of lacustrine methanotrophy fueled by oxidized S and/or Fe species, which likely derived from oxygenic and/or anoxygenic photosynthesis. Photosynthesis, followed by methanogenesis and methanotrophy may have been important in lakes at a time of supercontinent growth and eruption of large subaerial igneous provinces. In this context, anaerobic methanotrophy could have played a part in regulating atmospheric methane.